Peningkatan Pelayanan Kesehatan Lansia Melalui Pembinaan Kader Kesehatan Puskesmas Padang Kandis, Kab. 50 Kota Sumatera Barat - Irramah, Miftah; Afriwardi, Afriwardi; Amir, Arni; Anggraini, Fika Tri; Irawati, Lili; Ilhami, Yose Ramda; Syawqi, Rahmat; Lailani, Mutia; Sari, Desy Nofita (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
As the global population increases, the need for effective elderly care becomes increasingly urgent. Health cadres play a crucial role in improving the health and well-being of communities. One of the strategies to address this need is training health cadres, who can serve as vital links between healthcare providers and the elderly. In this training program, we aimed to enhance the role of health cadres in elderly care to support the physical, mental, and social well-being of the elderly. Through interactive exercises and providing health cadre pocketbooks, participants learned how to assess the individual needs of the elderly and increase their motivation to visit nearby healthcare facilities, thus improving the health status of the elderly in the region of Nagari Padang Kandis, district of 50 Kota. The activity involved 15 elderly health cadres. This training showed a 25% increase in the cadres' knowledge, as improved pre-test and post-test scores indicated. The health cadres now possess the skills and knowledge to effectively support the elderly community in their environment, fostering an independent and active elderly population in their daily activities and reducing dependence on the productive-age population. Furthermore, this community engagement activity, involving collaboration between the academic community of the Faculty of Medicine, Universitas Andalas, and the Padang Kandis health center, will be conducted periodically to enhance the health status of the local individuals in their society life.